Irving Penn - Centennial - Penn, Irving 1917-2009; Hambourg, Maria Morris 1949-; Rosenheim, Jeff L. (Schirmer Mosel, 2017)
"Celebrating the centennial of Irving Penn's birth, this volume spans the entirety of his groundbreaking career. The introduction situates his work in the context of the various artistic, social, and political environments and events that affected the content of his photographs. The essays acquaint readers with Penn's primary subjects and campaigns, including early documentary scenes and imagery; portraits; fashion; female nudes; people of Peru, Dahomey (Benin), New Guinea, and Morocco; still lifes; and more"--Provided by publisher
Diese Publikation erscheint anlässlich der Ausstellung 'Irving Penn: Centennial', die vom 20. April bis 30. Juli 2017 im Metropolitan Museum of Art, New York, gezeigt wird. Weitere Stationen sind das Grand Palais, Paris (21. September 2017-29. Januar 2018) und das Instituto Moreira Salles, São Paulo (Herbst 2018)
Keywords: Penn, Irving / Exhibitions; Penn, Irving -- 1917-2009; Geschichte 1948-2007; Geschichte 1939-2007; Photography, Artistic / Exhibitions; Mensch -- Motiv; Aktfotografie; Porträtfotografie; Fotografie; Mode; Photographie; Portraits; Ausstellungskatalog; Ausstellungskatalog -- Grand Palais -- 21.09.2017-29.01.2018 -- Paris; Ausstellungskatalog -- Instituto Moreira Salles -- Herbst 2018 -- São Paulo; Ausstellungskatalog -- Metropolitan Museum of Art -- 20.04.2017-30.07.2017 -- New York, NY; Bildband